PERSEPSI MASYARAKAT TERHADAP AKTIVITAS PENAMBANGAN GALIAN C DI BUKIT PENIRAMAN DESA PENIRAMAN KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Sari, Mulyani Puspita; Muin, Sudirman; Dirhamsyah, M (JURNAL HUTAN LESTARI, 2019)
Perception is a process that involves the entry of messages or information into the human brain. Through perception, human could connect constantly with their environment. Peniraman Village has natural resource potential in the form of type C trenching (Stone and Soil) which gives rise to various perceptions from the community. This study aims to determine the community perception towards type C trenching activities in Peniraman Hill and find out the relationship between the level of education, income and cosmopolitan factors. This study uses a survey method with observation, interviews and questionnaires containing a number of questions asked to the respondents, The data is collected using purposive random sampling. Analysis of the data is using descriptive analysis of the chi square test and inferential analysis using nonparametric statistical tests of the Kendall Tau correlation. The respondents in this study is 68 people. The results of this study indicate that people's perceptions tend to be positive, the level of income level is low, the level of cosmopolitan is moderate. There is a positive and significant correlation between education level and perception, and there is no significant correlation and there is no relation between the level of income and cosmopolitan levels with the community perception.Keywords: Community Perception, Mining, Peniraman Village